ANALISIS PENDAPATAN ASLI DAERAH DAN DANA PERIMBANGAN TERHADAP PERTUMBUHAN EKONOMI KABUPATEN KOTA DI SUMATERA BARAT - Aimon, Hasdi; Putra, Rova Luarta (Jurnal Kajian Ekonomi, 2015)
The study explained the effects of the original income of region on economic growth; and equilibrium funds (general allocation funds and special allocation funds) on regencies and city economic growth in West Sumatera.The type of research is the study causative. The data was conducted in 12th regencies and 7th cities in West Sumatra and time series 2009 to 2013. The analysis used Regression Panel Model (Pooled Analysis). The result show that the original income of region and general allocation funds significantly effect on economic growth, but Special allocation funds had no significant effect with the negative direction on regencies and city economic growth in West Sumatera. It’s recomended that the Government is explorated to the sources of revenues primarily to revenue (original income of region) because it’s a major source of financing that will to increase the economic growth of a region. Besides that, districts and cities in West Sumatra so much attention to the use of these funds, so that the assistance provided by the central government targeted and appropriate objectives was boost economic growth in each region.Keyword: Original income of region, Equilibrium funds, and Economic growth.